ما بين علم الوقاية وسد الذرائع: مقاربة مقاصدة بالتركيز على تعاطي المخدرات والمؤثرات العقلية Between Prevention Science and the Blocking of Means: A Maqasid-Based Approach in Relation to Drugs and Psychotropic Substances - El-Mesawi, Mohamed El-Tahir; AbouEldahab, Essam Ibrahim (IIUM Press, 2016)
Science of Prevention or Prevention Science is an inter-disciplinary field which aims to understand phenomena and deal with problems in a holistic way that engulfs their complex structure and diverse dimensions from different angles whereby the insights of more than one discipline consolidate each other. This science is of a recent birth and the history of its emergence does not go farther back than the early nineties or late eighties of the twentieth century. Its birth was necessitated by the social problems, pandemic diseases and environmental catastrophes that human societies underwent throughout the second half of the twentieth century. This called for the necessity of thinking not only about the ways and means of dealing with those problems, pandemics and catastrophes by controlling their effects and alleviating the severity of their impact, but it also required looking into the means of avoiding them by intervening to prevent their occurrence through the control of their causes. On the other hand, the Blocking of Means is one the important Islamic legislative rules which focus, both purpose and procedure wise, on preventing the happening of acts or events that will would cause physical or moral damage or corruption in the life of the individual and so-ciety. The Blocking of Means rule falls under one of the great principles of the SharÊÑah, namely the Consideration of Consequences. This principle does not content itself by dealing with social phenomena and human problems by just looking at them in their present status, but it most impor-tantly considers the possibilities of their future develo-pment and consequences, thus being informed by the integ-rated system of the Maqasid al-Shari'ah (Shari'ah goals) which revolve on the goodness of man and society in terms of bringing about benefit and warding off harm. Likewise, both Prevention Science and the doctrine of the Blocking of Means converge on one fundamental objective: to protect human so-ciety individually and collectively in the present as well as in the future. This is the main thesis the present study has attempted to expound. And since drugs are among the complicated problems that have affected contemporary societies in an escalating manner, the authors have deemed it appropriate to take it up as an empirical case to be consi-dered from an integrated perspective bringing together Prevention Science and the Blocking of Means. Key words: Prevention Science, Blocking of Means, Consideration of Consequences, Maqasid al-Shari'ah, integrated approach, drugs pandemic